The Impact of Motivation on Primary Education Teachers: A Study in Idemili South Local Government Area of Anambra State, Nigeria - Ann Ngozi Ugobueze (Action Research Journal Indonesia (ARJI), 2024)
This descriptive survey study explored the impact of motivation on primary education teachers in Idemili South LGA, Anambra State. It involved 140 teachers from eight schools, selected via simple random sampling. A 15-item structured questionnaire on a 4-point Likert scale was used for data collection, achieving full response rates. Data analysis utilized frequency and mean scores with a 2.5 cut-off for interpretation. The findings revealed that both intrinsic and extrinsic factors, such as fair remuneration, supportive working environments, public recognition, and access to professional development, significantly enhance teachers' motivation. Conversely, inadequate motivation due to low pay, lack of resources, and limited career advancement opportunities was found to negatively impact teachers' performance and increase turnover rates. The study highlights the importance of implementing strategies that foster teacher motivation to improve educational quality and student outcomes in the region. Recommendations were made for policymakers and educational administrators to prioritize teacher motivation as a means to enhance the sustainability of primary education.